(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The features derivational structure and semantics of botanical names on –ok were reviewed in the article and their place in the confixes subsystem of the Ukrainian nouns was determined. The activity of confixes was leant, specifically formants with the postpositive component –ok in the formation process of the botanical names.